Make gifts! - Solga, Kim. (Danbury, CT : Grolier, Inc., 1993)
Readers learn how to make a variety of craft gifts including jewelry, sculpture, cards, calendars, containers, wrapping paper, and more.
"For ages 6-11"--Cover p. 4.
Keywords: Handicraft; Gifts